Combination of mussel shell and potassium hydroxide as solid waste basic catalyst (SWBC) for fatty acid methyl ester (FAME) synthesis from castor oil - Nurul 'Adilah, Rosnan (2015)
Continuous use of fossil fuel can cause decreasing of fossil fuel resources and increase petroleum price. Biodiesel provide a great path in helping human to reduce the dependence on non-renewable petroleum derived fuel. Initially, biodiesel is produced from edible oil feedstock such as palm oil and as the demand for biodiesel ascending, the feedstock for food truncating thus pose a threat to food chain. The main purpose of this research is to synthesis fatty acid methyl ester (FAME) from castor oil. The effects of different catalysts, temperature and reaction time are also studied. Two catalysts were prepared, where mussel shell waste being calcined to produce calcium oxide (CaO) and then the other one CaO impregnated with potassium hydroxide (KOH) to produce solid waste basic catalyst (SWBC). The SWBC were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), and Thermal Gravimetric Analysis (TGA). The castor oil was converted into biodiesel through transesterification in a presence of methanol and two different SWBC. CaO/KOH was the best SWBC which yields, 91.17%, the highest biodiesel produced from Castor oil and had a potential to be an alternative low cost catalyst and at the same time improve the yield of FAME.